Viability of Lactobacillus acidophilus in Effervescent Granules Prepared via Wet Granulation Method: In Vitro Study (Sciences of Pharmacy, 2023)
Lactobacillus acidophilus, a strain of lactic acid bacteria widely used as a probiotic microorganism, has been extensively employed in developing probiotic products including in effervescent granules. This study's objectives were to ensure that the resultant granules possessed the desired physical attributes and retained the requisite viability of lactic acid bacteria. A wet granulation method was used. The formula was physically evaluated and analyzed using Design Expert software, followed by gram staining and bacterial harvesting. Gram staining verification demonstrated the gram-positive nature of the pure L. acidophilus bacterial isolates, as evidenced by their consistent purple coloration and characteristic basil shape. Evaluation of physical properties revealed organoleptic attributes such as granular shape, white coloration devoid of odor, flow rate of 1.497 g/sec, an angle of repose at 40.75o, compressibility of 11.45%, drying loss of 0.62%, and a foam height of 3.075 cm, consistently meeting the stipulated criteria. Furthermore, formula I, II, and III preserved L. acidophilus bacteria after being converted into effervescent granules, as evidenced by viable lactic acid bacteria counts, with formula I (412.5 x 101 cfu/g), formula II (422.7 x 101 cfu/g), and formula III (highest at 522.7 x 101 cfu/g). The formula I emerges as the most favorable effervescent granules containing L. acidophilus 3%; polyvinylpyrrolidone 3%; citric acid 0.3%; tartaric acid 49.7%; sodium bicarbonate 25% and lactose as filler. Based on the finding, this probiotic effervescent granules has the potential to be developed as a daily supplement, especially for flora normal stabilization.